PROTOTYPE ALAT PENGERING SEPATU BERBASIS ARDUINO UNTUK MENUNJANG USAHA CUCI SEPATU SUKLIN.ID - Anggito Wito Utomo Anggito (Jurnal Informatika dan Teknik Elektro Terapan, 2026)
The growth of shoe cleaning service businesses requires technological innovation to improve operational effectiveness, particularly in the drying process which still depends on weather conditions, resulting in unstable processing time and reduced productivity. This study aims to design and implement an Arduino-based shoe dryer prototype that operates automatically, safely, and efficiently to support the operations of the Suklin.id shoe cleaning business. The research employed the waterfall method, consisting of requirement, design, implementation, verification, and maintenance stages. The system was built using Arduino Uno as the main microcontroller, a DHT11 sensor for temperature and humidity detection, a PTC heater and incandescent lamp as heat sources, a fan for air circulation, a relay as an actuator controller, and a limit switch with a buzzer as a door safety system. An automatic safety mechanism disconnects the power supply when the temperature exceeds the set threshold. Testing results show that the prototype dried canvas shoes at an average temperature of 35.8°C within 1 hour 39 minutes, and synthetic leather shoes at 32.2°C within 1 hour 15 minutes. Compared with the conventional method, the system achieved a time efficiency of 72.50% for canvas shoes and 68.75% for synthetic leather shoes. The developed prototype is therefore proven to improve drying efficiency and reduce dependency on weather conditions.